Review of The Completeness of Filling In Informed Consent on Sectio Caesarea Action at Cilegon Hospital in 2023 - Erwin Muhtaruddin; Evi Avicenna Agustin; Nur Rahma Hasanah (Journal Of Applied Health Research And Development, 2023)
At the Cilegon City Hospital, there were several Informed Cosent forms which were incomplete, especially when filling in the identification of the patient and the person in charge of the patient and authentication of the doctor and the person in charge of the patient. The purpose of this study was to identify patient identity, authentication and important reports and to find out the factors causing the incomplete filling of Informed Consent. This type of research uses quantitative descriptive research. The population in this study is the object population and the subject population and the sample in this study is the object sample and the subject sample. The average completeness of patient identity on the informed consent sheet was 96% and incompleteness was 4%, the average completeness of authentication was 81% and incompleteness was 19%, the average completeness of important reporting was 100% and incompleteness was 0%. Factors causing the incompleteness of filling out the informed consent sheet were because the doctor was in a hurry to fill out the informed consent and the lack of socialization and evaluation of the importance of filling out the complete informed consent. It is expected that the hospital should carry out periodic socialization and evaluation of the importance of filling out complete Informed Consent as well as monitoring.